2000
DOI: 10.1029/1999jd900932
|View full text |Cite
|
Sign up to set email alerts
|

A polar stratospheric cloud parameterization for the global modeling initiative three‐dimensional model and its response to stratospheric aircraft

Abstract: Abstract. We describe a new parameterization of polar stratospheric clouds (PSCs) which was written for and incorporated into the three-dimensional (3-D) chemistry and transport model (CTM) developed for NASA's Atmospheric Effects of Aviation Project (AEAP) by the Global Modeling Initiative (GMI). The parameterization was designed to respond to changes in NO s and H20 produced by high-speed civilian transport (HSCT) emissions. The parameterization predicts surface area densities (SADs) of both Type 1 and Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 46 publications
1
89
0
Order By: Relevance
“…The converse is true for cold winters. The relationship between dynamical variability and O 3 was demonstrated by Randel et al [2002], who showed the link between changes in stratospheric wave driving (i.e., the Eliassen-Palm flux) and ozone transport to high latitudes in spring, concluding that hemispheric ozone trends were caused in part by the wave driving trends from 1979-2000. Chipperfield and Jones [1999 also observed this relationship and concluded that dynamical variability in the 1990s contributed more to IA variability in March Arctic O 3 than chemical loss.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The converse is true for cold winters. The relationship between dynamical variability and O 3 was demonstrated by Randel et al [2002], who showed the link between changes in stratospheric wave driving (i.e., the Eliassen-Palm flux) and ozone transport to high latitudes in spring, concluding that hemispheric ozone trends were caused in part by the wave driving trends from 1979-2000. Chipperfield and Jones [1999 also observed this relationship and concluded that dynamical variability in the 1990s contributed more to IA variability in March Arctic O 3 than chemical loss.…”
Section: Introductionmentioning
confidence: 92%
“…Details of the GMI CTM including chemical mechanism can be found in Strahan et al [2007] and Duncan et al [2007]. The stratospheric chemical mechanism [Douglass and Kawa, 1999] and the polar stratospheric cloud parameterization [Considine et al, 2000] used in GMI are the same as those used in the GEOS chemistry climate model (GEOSCCM). The SPARC Chemistry Climate Model validation activity [SPARC, 2010] determined that GEOSCCM produced Antarctic O 3 loss consistent with observations.…”
Section: Mls Observations and The Gmi Ctmmentioning
confidence: 99%
“…More information about the GMI 3-D CTM and its chemical mechanism can be found in Strahan et al (2007) and Duncan et al (2007). The stratospheric chemical mechanism is taken from Douglass and Kawa (1999) and the polar stratospheric cloud parameterization is described in Considine et al (2000).…”
Section: Description Of the Gmi 3-d Ctmmentioning
confidence: 99%
“…To achieve this goal the GMI is developing and utilizing atmospheric models which facilitate the testing of model sensitivities and uncertainties, and subjecting the models to extensive evaluation against observations of atmospheric composition. The GMI produced a CTM appropriate for stratospheric assessments (Rotman et al, 2001), which was used to evaluate the potential effects of stratospheric aircraft on the global stratosphere ) and on the Antarctic lower stratosphere (Considine et al, 2000). An improved version of this model was used more recently in several sensitivity studies of the stratosphere and stratospheric response to anticipated decreases in stratospheric chlorine loading (Considine et al, 2004a;Douglass et al, 2004;Strahan and Douglass, 2004).…”
Section: Introductionmentioning
confidence: 99%